PEMBARUAN HASSAN HANAFI: TANTANGAN MODERNITAS FILSAFAT SKEPTISISME BERBANDING TERBALIK TERHADAP KEBANGKITAN ISLAM - Zulkarnain, Zulkarnain; Adenan, Adenan; Kamdani, Kamdani (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
The revival of Islam is an inevitability, not only because of the dominance of Western factors that have lasted seven centuries, but olso the urgent need between the challenges of modernity and the condition of backwardness of Muslims in global relations. Hassan Hanafi initiated Islamic Reform which he believed was a solution. This research aims to analyze in depth the phenomenon of Hasan Hanafi's Islamic Left from philosophical, sociological and political perspectives, and the philosophy of skepticism as a source of Islamic revival. Data collection techniques were carried out through exploration and critical analysis of various literature related to the research topic. Data sources include primary, namely the ideas of "Islamic Left" (al-Yasar al-Islam) Hasan Hanafi and the book History of Western Philosophy and Its Connection with Political and Social Circumtances From the Early Times to the Present Day, the work of Bertrand Russell, and secondary sources ; scientific journals and previous research. The basic reason for confronting the Hanafi Islamic Left concept and the philosophy of skepticism as a paradoxical attitude is to obtain logistical and critical arguments that can be justified conceptually and academically. As a result, the renewal of Muslim society from the Hanafi perspective is indeed necessary for the revival of Islam, while the philosophy of skepticism is inversely proportional to the progress of civilization